Digital competences and soft skills of university students in e-learning in times of COVID-19 - Loayza-Maturrano, Edward Faustino (2023)
Technology-enabled learning is an opportunity that arises from the need caused by social confinement in times of the COVID-19 pandemic. The objective of the study is to determine the characteristics of the digital competences of university students, which allows the effectiveness of their training in distance education. The work compares the level of digital skills of students with the level of development of soft skills that guarantee the quality of learning in a remote education environment. A questionnaire of thirty-three questions was applied to a sample of 116 undergraduate students from five professional careers from a public university in order to describe the characteristics of the levels of digital skills and interpret their relationship with soft skills. The results show that despite the high level of students’ digital skills, they do not use all these skills in the electronic educational environment in the pandemic period. It is concluded in the study that the most complex and important skills related to the independent acquisition of information, the planning of one’s own work, and the soft skills related to team interaction, communication with others, among their peers, teachers and administration are the least developed in the majority of respondents.